2022
DOI: 10.3389/fpsyg.2022.940978
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of multimorbidity and some psychiatric disorders: A systematic review of the literature

Abstract: Objective: The presence of two or more chronic diseases results in worse clinical outcomes than expected by a simple combination of diseases. This synergistic e ect is expected to be higher when combined with some conditions, depending on the number and severity of diseases. Multimorbidity is a relatively new term, with the first fundamental definitions appearing in . Studies usually define it as the presence of at least two chronic medical illnesses. However, little is known regarding the relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Multimorbidity is indicated by the presence of 2 or more of the diseases in a single individual. The diagnosis of chronic conditions was based on whether the respondent had ever been diagnosed with a chronic disease by a doctor and received treatment for that disease [ 3 , 7 , 8 ]. When the prevalence of multimorbidity is low, the sample size for certain combinations of multimorbid conditions may be insufficient to provide reliable results [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Multimorbidity is indicated by the presence of 2 or more of the diseases in a single individual. The diagnosis of chronic conditions was based on whether the respondent had ever been diagnosed with a chronic disease by a doctor and received treatment for that disease [ 3 , 7 , 8 ]. When the prevalence of multimorbidity is low, the sample size for certain combinations of multimorbid conditions may be insufficient to provide reliable results [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…Health-related quality of life (HRQoL) is an important health outcome indicator in the aging process. Previous observational studies have shown the negative effects of multimorbidity on HRQoL [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that depression is associated with multimorbidity, the occurrence of two or more chronic diseases. It has been shown that the direction of this association seems to run from multimorbidity to depression 4,5 . As individuals age, they tend to become alone, losing friends and family members, which renders them susceptible to depressive symptoms 6 .…”
Section: Introductionmentioning
confidence: 99%
“…There is an ongoing effort of trying to identify patterns of clustering for these conditions, which varies significantly across studies 12 . A three-cluster pattern seems to be emerging, with musculoskeletal, cardiometabolic, and neuropsychiatric clusters 4,12 . Furthermore, being overweight is associated with multimorbidity in a dose-response pattern.…”
Section: Introductionmentioning
confidence: 99%